Relationship between Immune Parameters and Organ Involvement in Children with Henoch-Schonlein Purpura - Pan, Yan-xiang; Ye, Qing; Shao, Wen-xia; Shang, Shi-qiang; Mao, Jian-hua; Zhang, Ting; Shen, Hong-qiang; Zhao, Ning (PloS one, 2014)
Henoch-Schonlein purpura (HSP) is the most common type of connective tissue diseases which increasingly occurs in children in recent years and its pathogenesis remains unclear. In order to explore the immune parameters and underlying pathogenesis mechanism of children with HSP, the study involved 1232 patients with HSP having different clinical symptoms and their laboratory indicators were evaluated. Th1/Th2 imbalance and overactivity of Th2 cells can cause increase in the synthesis and release of immunoglobulins in children with HSP. The number of red blood cells and white blood cells in urine was directly proportional to the level of IgA and inversely proportional to the level of serum complements (C3 and C4). Activation of these complements caused by immunoglobulin in patients with HSP plays an important role in renal injury. The urinary protein content in children with HSP along with proteinuria was positively correlated with IgE level, and IgE mediated type 1 hypersensitivity can cause increase in capillary permeability and weakened the charge barrier; hence, it could be considered as one of the causes of proteinuria in HSP. Additionally, the NK cells percentage was reduced and impaired immune function of NK cells were related to the immune injury of the digestive tract and kidney.